SUPLEMENTASI INULIN DALAM PAKAN TERHADAP KELIMPAHAN BAKTERI ASAM LAKTAT, KINERJA PERTUMBUHAN DAN PEMANFAATAN PAKAN IKAN NILA (Oreochromis niloticus) - Pamungkas, Panji Krisna Yuga; Agustina; Sulistyawati; Agustina, Agustina (University of Prof. Dr. Hazairin, SH, 2024)
Inulin is a type of prebiotic that has been studied to be useful in increasing the growth of several fish species. This research was carried out to evaluate the effect of inulin supplementation on the abundance of lactic acid bacteria in the intestine, growth performance and feed utilization including weight growth, specific growth rate, and feed conversion ratio of tilapia (Oreochromis niloticus) fingerlings. Ten tilapia fish with an average weight of 4.41 ± 0.52 g were reared in plastic tanks with a volume of 30 L for 30 days. During rearing, tilapia are given commercial feed with inulin supplementation as a treatment, namely: 0.0; 1.5; 3.0 and 6.0 g/kg feed, three times a day ad satiation. The data obtained in this study was tested statistically using the one-way ANOVA test and Tukey's advanced test. The results of the study showed that the inulin supplementation treatment of 1.5 g/kg feed provided the highest abundance of lactic acid bacteria at the end of the study, the highest weight growth, specific growth rate and lowest feed conversion ratio (P<0.05) compared to other treatments. The highest total gut bacteria of tilapia fry at the end of the study was shown at a treatment dose of 3.0 g inulin/kg feed. Based on this, inulin at a dose of 1.5 g/kg feed can be used as a prebiotic for tilapia seeds to support their growth and feed utilization.